Answered

Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Given the conditional statement [tex]\(\sim p \rightarrow q\)[/tex], which statement is logically equivalent?

A. [tex]\(p \rightarrow \sim q\)[/tex]
B. [tex]\(\sim p \rightarrow \sim q\)[/tex]
C. [tex]\(\sim q \rightarrow \sim p\)[/tex]
D. [tex]\(\sim q \rightarrow p\)[/tex]


Sagot :

To determine which statement is logically equivalent to the conditional statement [tex]\(\sim p \rightarrow q\)[/tex], we need to understand logical equivalences and how they can be used to transform the given statement.

### Step-by-Step Solution:

1. Original Statement Analysis:
- The given statement is [tex]\(\sim p \rightarrow q\)[/tex].
- To find an equivalent statement, we use the fact that an implication [tex]\(A \rightarrow B\)[/tex] can be rewritten using the equivalence:
[tex]\[ A \rightarrow B \equiv \sim A \vee B \][/tex]

2. Apply the Equivalence:
- For the statement [tex]\(\sim p \rightarrow q\)[/tex], treat [tex]\(\sim p\)[/tex] as [tex]\(A\)[/tex] and [tex]\(q\)[/tex] as [tex]\(B\)[/tex].
- So, [tex]\[\sim p \rightarrow q \equiv \sim (\sim p) \vee q\][/tex]

3. Simplify the Expression:
- Simplifying [tex]\(\sim (\sim p)\)[/tex] gives [tex]\(p\)[/tex].
- Thus, [tex]\[\sim p \rightarrow q \equiv p \vee q\][/tex]

4. Compare with Given Choices:
- Now we need to compare [tex]\(p \vee q\)[/tex] with the equivalent forms of the given choices:
1. [tex]\(p \rightarrow \sim q\)[/tex]
2. [tex]\(\sim p \rightarrow \sim q\)[/tex]
3. [tex]\(\sim q \rightarrow \sim p\)[/tex]
4. [tex]\(\sim q \rightarrow p\)[/tex]

5. Transform Each Choice:
- Let's find the logical equivalences for each option in terms of [tex]\(p\)[/tex] and [tex]\(q\)[/tex]:
1. [tex]\(p \rightarrow \sim q\)[/tex] is equivalent to [tex]\(\sim p \vee \sim q\)[/tex]
2. [tex]\(\sim p \rightarrow \sim q\)[/tex] is equivalent to [tex]\(p \vee \sim q\)[/tex]
3. [tex]\(\sim q \rightarrow \sim p\)[/tex] is equivalent to [tex]\(q \vee p\)[/tex] (which is logically equivalent to [tex]\(p \vee q\)[/tex])
4. [tex]\(\sim q \rightarrow p\)[/tex] is equivalent to [tex]\(q \vee \sim p\)[/tex]

6. Check for Equivalence:
- We need the form [tex]\(p \vee q\)[/tex], which matches exactly with the form obtained from the given statement [tex]\(\sim p \rightarrow q\)[/tex].

From the transformed logical forms, we see that option 2:
[tex]\(\sim p \rightarrow \sim q \equiv p \vee q\)[/tex] fits our derived form.

Therefore, the statement logically equivalent to [tex]\(\sim p \rightarrow q\)[/tex] is:
[tex]\[ \boxed{\sim p \rightarrow \sim q} \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.